The Readiness of Islamic Religious Education Teachers to Enter The Era of Industrial Society 5.0 - Budi Santoso; Triono, Mukhlas; Ash Shiddiq, Muhammad Abdurahman; Arifin, Syamsul (Pascasarjana Universitas KH. Abdul Chalim, 2024)
The challenges of entering the era of Society 5.0 require people to face more complex challenges. These changes have both positive and negative impacts. In connection with the progress of Society 5.0, educational institutions have new challenges, namely not only making their students academically ready but also printing them with character. The development of the world of communication today requires people to face various complex challenges. The era of society 5.0 has an impact on all human life, both positive and negative. In this context, educational institutions are expected to be pivotal in addressing the challenges. This can be achieved by equipping students with a comprehensive understanding of religious studies. This research is included in library research using the content analysis method. This research used the following procedures: Preparing tools, preparing the work bibliography, timing, analysis, and compiling research notes. The data in the study were obtained from literature in accordance with the research topic. The new concept emerges, intact and up-to-date, from the collected and processed data. This includes gathering references manually and digitally. This research indicates that educators must prepare themselves to face the challenges of the Society 5.0 era. This preparation should entail two key areas of focus, namely character education, which at least includes five characters: religious, independent, nationalist, integrity, and cooperation, and links learning with critical thinking skills.